The Epstein-Barr Virus Oncoprotein Latent Membrane Protein 1 Engages the Tumor Necrosis Factor Receptor-Associated Proteins TRADD and Receptor-Interacting Protein (RIP) but Does Not Induce Apoptosis or Require RIP for NF-κB Activation - Izumi, Kenneth M. (American Society for Microbiology (ASM), 1999)
A site in the Epstein-Barr virus (EBV) transforming protein LMP1 that constitutively associates with the tumor necrosis factor receptor 1 (TNFR1)-associated death domain protein TRADD to mediate NF-κB and c-Jun N-terminal kinase activation is critical for long-term lymphoblastoid cell proliferation. We now find that LMP1 signaling through TRADD differs from TNFR1 signaling through TRADD. LMP1 needs only 11 amino acids to activate NF-κB or synergize with TRADD in NF-κB activation, while TNFR1 requires ∼70 residues. Further, LMP1 does not require TRADD residues 294 to 312 for NF-κB activation, while TNFR1 requires TRADD residues 296 to 302. LMP1 is partially blocked for NF-κB activation by a TRADD mutant consisting of residues 122 to 293. Unlike TNFR1, LMP1 can interact directly with receptor-interacting protein (RIP) and stably associates with RIP in EBV-transformed lymphoblastoid cell lines. Surprisingly, LMP1 does not require RIP for NF-κB activation. Despite constitutive association with TRADD or RIP, LMP1 does not induce apoptosis in EBV-negative Burkitt lymphoma or human embryonic kidney 293 cells. These results add a different perspective to the molecular interactions through which LMP1, TRADD, and RIP participate in B-lymphocyte activation and growth.